Pengaruh Likuiditas, Operating Cash Flow, dan Risiko Penyisihan Piutang Tak Tertagih terhadap Stabilitas Keuangan Emiten IDX Perbankan Periode 2020–2023 - Jihan Rahmah Fadiyah; Sumarno M.; Murti Wijayanti (Jurnal Kendali Akuntansi, 2026)
This study aims to analyze the effect of liquidity, Operating Cash Flow (OCF), and the risk of allowance for uncollectible accounts on the financial stability of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The research employed a quantitative approach based on Signaling Theory. The data were obtained from the financial statements of banking companies that met the sampling criteria throughout the observation period. Data analysis was conducted using inferential statistical techniques to examine the partial and simultaneous effects of the independent variables on financial stability. The findings indicate that liquidity and Operating Cash Flow (OCF) do not have a significant effect on financial stability. In contrast, the risk of allowance for uncollectible accounts has a positive and significant effect on financial stability. Simultaneously, the three independent variables significantly influence the financial stability of banking companies. These findings suggest that credit risk management, particularly through the allowance for uncollectible accounts, plays a more dominant role in maintaining financial stability than liquidity and operating cash flow. This study contributes to the development of financial management literature and provides useful insights for corporate management, investors, and other stakeholders in evaluating the financial stability of companies in the banking sector.